Biotinylation of reducing and non-reducing termini to create plug-and-play polysaccharides. (1st April 2023) - Mohandas, Nimisha; Edwards, Patrick J.B.; Kent, Lisa M.; Jameson, Geoffrey B.; Williams, Martin A.K.
Abstract: Single-molecule studies continue to grow in popularity. In cases where biopolymer samples of interest exhibit variations in fine-structure between individual chains such single-molecule studies uniquely offer the promise of revealing deep structure-function relationships. Polysaccharides are typically studied in bulk and, as such, their study could greatly benefit from the application of single-molecule techniques. However, while for example single-molecule optical tweezers (OT) studies have become commonplace for DNA, studies of polysaccharides have lagged behind somewhat, complicated by the difficulty of studying molecules that amongst other things have more complex end-group chemistry. Recently, divalent streptavidin linkers have been shown to be capable of concatenating two pieces of biotin-terminated DNA to produce robust composite strings that run intact through conventional gels, and can be used in single-molecule OT experiments (Mohandas, Kent, Raudsepp, Jameson, & Williams, 2022). By using two such streptavidin linkers, biotin-terminated polymers could be inserted between two sections of DNA in order to facilitate single-molecule experiments on biopolymers that are currently difficult to address by other means. Here, we describe a generic approach for placing the required biotin moieties at both ends of polysaccharide chains, producing plug-and-play polysaccharide inserts that can be incorporated into composite polymer strings using streptavidin linking hubs. Graphical abstract: Unlabelled Image